The use of alginate as a potential chondrogenic differentiation promoter of mesenchymal stromal cells and its application / Havva Dashtdar - Havva, Dashtdar (2014)

(untitled)
Alginate culture system offers an ideal 3-Dimensional microenvironment for the re-differentiation of chondrocytes following its isolation from its environment and 2D culture expansion. It has also been shown that this material supports chondrogenesis for mesenchymal stromal cells in vitro. Bone marrow-derived mesenchymal stromal cells (MSCs) have been considered a potential cell source for cartilage repair. However, successful translation of such stem cell therapy into clinical trials using alginate as a carrier requires better understanding of the complex processes involved in the differentiation of MSCs. Changes in chondrogenic microenvironment may induce different outcomes during chondrogenesis, i.e. either stable chondrocyte-like phenotype or terminally differentiated hypertrophic chondrocytes, which may result in endochondral ossification formation following transplantation in vivo. Moreover there remains a question as to whether non-induced or lineage-committed MSCs should be applied for cartilage tissue engineering. Therefore the present thesis was conducted in 3 main studies to investigate the use of alginate as a scaffold or cell carrier in chondrogenic differentiation of mesenchymal stromal cells and cartilage repair. In the first study, chondrogenic differentiated MSCs were characterized using morphological, biochemical and ultra-structural analyses. In the second study, expression of chondrogenic genes and adhesion molecules in alginate culture, pellet culture and 2D monolayer were compared using real-time RT-PCR. In the third study, alginate was transplanted with or without mesenchymal stromal cells in rabbit knee focal cartilage defects to determine whether chondrogenic MSCs, non-induced MSCs, or alginate alone will result in superior repair outcome in full thickness cartilage damage. iv The results of the first part of the study demonstrated superior chondrogenic differentiation in the alginate group, indicated by the higher cell viability and production of chondrogenic markers of sulphated glycosaminoglycan and collagen type II as compared to monolayer or pellet cultures. Ultrastructural studies further revealed detailed cell structures, cell-matrix interactions and cell viability in 3D structures during chondrogenic differentiation. In the second part of the study, chondrogenic and hypertophic gene analysis demonstrated the hypertrophic nature of chondrogenesis in 2D monolayer and 3D pellet culture while non-hypertrophic features were observed in alginate. In the third study, the application of alginate in cartilage repair either as a carrier for undifferentiated MSCs or as a scaffold for chondrogenic differentiation of MSCs before being transplanted, improved the cartilage repair outcome in rabbit knees. However there were no differences observed in the outcome following transplantation of alginate alone in cartilage defects compared to the non-treated knee. In conclusion, the present thesis suggests that alginate may prove to be a potential biomaterial that provides a favourable environment for chondrogenic differentiation of MSCs in vitro and in vivo, thereby proving itself as a potential candidate scaffold/cell carrier for clinical application involving the repair of damaged cartilage.